Ideas and Applications Toward Sample Preparation for Food and Beverage Analysis - Stauffer, Mark T. (IntechOpen, 2017)
The goal of this book is to present an overview of applications and ideas toward sample preparation methods and techniques used in analysis of foods and beverages. This text is a compilation of selected research articles and reviews dealing with current efforts in the application of various methods and techniques of sample preparation to analysis of a variety of foods and beverages. The chapters in this book are divided into two broad sections. Section 1 deals with some ideas for methods and techniques that are applicable to problems that impact the analysis of foods and beverages and the food and beverage industries overall. Section 2 provides applications of sample preparation methods and techniques toward determination of specific analytes or classes of analytes in various foods and beverages. Overall, this book should serve as a source of scientific information for anyone involved in any aspect of analysis of foods and beverages.